Hand Sanitizers Marketed in the Streets of Addis Ababa, Ethiopia, in the Era of COVID-19: A Quality Concern - Selam MN (Risk Management and Healthcare Policy, 2020)
Muluken Nigatu Selam Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Muluken Nigatu SelamDepartment of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaTel +251 912159807Email muluken.nigatu@aau.edu.etAbstract: Hand hygiene is one of the least expensive measures proven to be effective in preventing the transmission of coronavirus disease 2019 (COVID-19). When access to handwashing facilities is limited, hand sanitizers offer a viable alternative for hand hygiene. Since the appearance of the first case of COVID-19 in Ethiopia, the demand for hand sanitizers, especially alcohol-based handrubs (ABHRs), was found to be increased. In the country, more than 100 manufacturers are engaged in the production of ABHRs. Besides, there are similar products without labels available for sale in the streets of Addis Ababa for which their nature and source are not clearly known. Generally, hand sanitizers marketed in the streets of the city are against the country’s regulatory requirement. The Ethiopian Food and Drug Authority should inspect manufacturers regularly and evaluate the quality of hand sanitizers in the market, especially those obtained from the streets of the city, and take appropriate measures on those products and manufacturers which fail to meet the regulatory requirements.Keywords: alcohol-based handrubs, quality, COVID-19, Addis Ababa, streets